2017
DOI: 10.1063/1.4984137
|View full text |Cite
|
Sign up to set email alerts
|

All-fiber-optic vector magnetometer based on anisotropic magnetism-manipulation of ferromagnetism nanoparticles

Abstract: The development of simple and sensitive sensors with the capability of simultaneously detecting magnetic field intensity and its direction in three-dimensional (3D) space is a technical imperative for magnetic field detection. In this paper, we first demonstrated the mechanism of anisotropic manipulation of ferromagnetism nanoparticles (FMNPs) in a non-continuous magnetic fluid film with the aid of varying magnetic fields. Second, based on the anisotropic distribution of the FMNPs around an optical fiber, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…When exposed to an applied magnetic field, the MNPs in the MF become magnetic dipoles and aggregate, forming stable chain-like structures oriented along the applied magnetic field direction [3]. However, the optical fiber in the MF destroys the original equilibrium state, forcing the MNPs to realign and form a new distribution around the fiber [23]. Moreover, the MNPs aggregate in an anisotropic manner: when the fiber surface is parallel (perpendicular) to the magnetic-field direction, they tend to gather to (depart from) the fiber surface [21,22].…”
Section: Principles and Structurementioning
confidence: 99%
See 1 more Smart Citation
“…When exposed to an applied magnetic field, the MNPs in the MF become magnetic dipoles and aggregate, forming stable chain-like structures oriented along the applied magnetic field direction [3]. However, the optical fiber in the MF destroys the original equilibrium state, forcing the MNPs to realign and form a new distribution around the fiber [23]. Moreover, the MNPs aggregate in an anisotropic manner: when the fiber surface is parallel (perpendicular) to the magnetic-field direction, they tend to gather to (depart from) the fiber surface [21,22].…”
Section: Principles and Structurementioning
confidence: 99%
“…This work revealed a new way to detect both the magnitude and orientation of a magnetic field. By creating a non-circularly-symmetric light-field in a fiber, Yin et al (2017) [22,23] developed two MF-based magnetic-vector sensors by sandwiching a piece of double-clad photonic-crystal-fiber or a thin core fiber between two single-mode fibers with a lateral offset. In 2018, based on a similar mechanism, magnetic-vector sensing was achieved by Layeghi et al, who used a tapered Hi-Bi fiber inserted in a fiber loop mirror [24].…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen that, besides the fundamental frequency there is only one main frequency component in the Fourier frequency spectra of a single S-tapered fiber interferometer, and therefore it could be regarded as a two-mode fiber interferometer with a periodic interferometric spectrum. When certain magnetic field is applied, magnetic particles will be magnetized to form a nanochain-like structure paralleled to the field direction [36]. Phase separation will occur during this process, causing the variation in effective dielectric constant [37].…”
Section: Experimental Setup and Operation Principlementioning
confidence: 99%
“…The field of magnetic sensors has seen rapid progress, Wang et al [2] demonstrated a magnetic sensor based on dual-core PCF. Chen et al [3] formed a sensor based on anisotropic of magnetic fluid (MF) particles. A Mach-Zehnder Interferometer (MZI) fiber was coated with MF to build a sensor [4].…”
Section: Introductionmentioning
confidence: 99%